2020
DOI: 10.1093/mnras/stz3520
|View full text |Cite
|
Sign up to set email alerts
|

Ozone chemistry on tidally locked M dwarf planets

Abstract: We use the Met Office Unified Model to explore the potential of a tidally locked M dwarf planet, nominally Proxima Centauri b irradiated by a quiescent version of its host star, to sustain an atmospheric ozone layer. We assume a slab ocean surface layer, and an Earth-like atmosphere of nitrogen and oxygen with trace amounts of ozone and water vapour. We describe ozone chemistry using the Chapman mechanism and the hydrogen oxide (HOx, describing the sum of OH and HO2) catalytic cycle. We find that Proxima Centa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(85 citation statements)
references
References 50 publications
(65 reference statements)
5
74
0
Order By: Relevance
“…Concerted studies in 3D are required to explore the interaction of the stellar activity with the atmosphere, and in particular, the potential impacts on the O 3 distribution, given that tidal locking gives rise to a permanent day-and nightside, the latter never receiving direct stellar radiation. This work has begun for quiescent host stars (Yates et al 2020), and we are working on extending it to include host star activity. Furthermore, the atmospheric composition in our simulations was kept constant in a simplified Earth-like configuration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Concerted studies in 3D are required to explore the interaction of the stellar activity with the atmosphere, and in particular, the potential impacts on the O 3 distribution, given that tidal locking gives rise to a permanent day-and nightside, the latter never receiving direct stellar radiation. This work has begun for quiescent host stars (Yates et al 2020), and we are working on extending it to include host star activity. Furthermore, the atmospheric composition in our simulations was kept constant in a simplified Earth-like configuration.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially important climate processes or mechanisms have also been omitted, such as atmospheric chemistry (e.g. ozone in Yates et al 2020), land-surface impact (e.g. Lewis et al 2018), dust (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variation of this magnitude is unlikely to be detectable with existing instrumentation, but an ozone column oscillation may be larger in amplitude on a tidally locked planet than on Earth, in line with our simulation results for water vapour. Studies of ozone photochemistry on tidally locked planets (Yates et al 2020) have also shown that the planet's nightside accumulates ozone in its cold traps, resulting in a zonally asymmetrical ozone layer without analogy on Earth and high levels of ozone in one hemisphere. Future work could explore how this tidally locked ozone chemistry would interact with oscillations in dayside production of ozone through stratospheric photochemistry.…”
Section: Oscillations In Meteorological and Atmospheric Compositionmentioning
confidence: 99%